Echocardiographic Evaluation of Initial Ambrisentan Plus Phosphodiesterase Type 5 Inhibitor on Right Ventricular Pulmonary Artery Coupling in Severe Pulmonary Arterial Hypertension Patients - Lan, Wei-Fang; Deng, Yan; Wei, Bin; Huang, Kai; Dai, Ping; Xie, Shan-Shan; Wu, Dan-dan (Frontiers in Cardiovascular Medicine, 2022)
Abstract Introduction: ambrisentan and phosphodiesterase type 5 inhibitor (PDE5i) have been approved for treating patients with pulmonary arterial hypertension (PAH). Echocardiographic right ventricular pulmonary artery coupling (RVPAC) has been shown to be a valid noninvasive and alternative measurement method to assess the predicted outcomes in PAH patients. The aim of this study was to study the effect and clinical correlates of initial ambrisentan plus PDE5i combination therapy on RVPAC in patients with severe PAH. Method and Results: We retrospectively studied and analyzed comprehensive clinical data, hemodynamics, and echocardiography in 27 patients with severe PAH before and after 6 months of initial combination therapy. Compared with the baseline, significant improvements in RVPAC ratios were observed, including RVFAC/PASP (0.31 ± 0.10 vs. 0.44 ± 0.15 %/mmHg, p < 0.001), TAPSE/PASP (0.15 ± 0.05 vs. 0.21 ± 0.06 mm/mmHg, p =0.001), S′/PASP (0.10 ± 0.03 vs. 0.14 ± 0.05 cm/s•mmHg, p =0.001), and RVSV/RVESV (0.79 ± 0.22 vs. 1.02 ± 0.20, p < 0.001). Functional status indices (World Health Organization functional classifications (WHO-FC) and 6 min walk distance (6MWD) and N-terminal pro B-type natriuretic peptide (NT-proBNP) levels) showed significant improvements. Right heart catheterization (RHC) evaluations for hemodynamic measurements between baseline and the 6-12 month follow-up were sPAP (96 ± 22 vs. 86 ± 24 mmHg, p = 0.002), mPAP (64 ± 18 vs. 56 ± 17 mmHg, p < 0.001) and TPVR (17.3 ± 6.7 vs. 12.1 ± 5.4 WU, p = 0.001). Simultaneously, significant associations between RVPAC ratios and NT-proBNP levels and WHO-FC and 6MWD were observed. Conclusions: Ambrisentan plus PDE-5i combination therapy resulted in a significant improvement in RVPAC in severe PAH. Importantly, RVPAC parameters correlated with known prognostic markers of PAH.